Manipulation of IRE1-Dependent MAPK Signaling by a Vibrio Agonist-Antagonist Effector Pair - Nicole J. De Nisco (American Society for Microbiology, 2021)
ABSTRACT Diverse bacterial pathogens employ effector delivery systems to disrupt vital cellular processes in the host (N. M. Alto and K. Orth, Cold Spring Harbor Perspect Biol 4:a006114, 2012, https://doi.org/10.1101/cshperspect.a006114). The type III secretion system 1 of the marine pathogen Vibrio parahaemolyticus utilizes the sequential action of four effectors to induce a rapid, proinflammatory cell death uniquely characterized by a prosurvival host transcriptional response (D. L. Burdette, M. L. Yarbrough, A Orvedahl, C. J. Gilpin, and K. Orth, Proc Natl Acad Sci USA 105:12497–12502, 2008, https://doi.org/10.1073/pnas.0802773105; N. J. De Nisco, M. Kanchwala, P. Li, J. Fernandez, C. Xing, and K. Orth, Sci Signal 10:eaa14501, 2017, https://doi.org/10.1126/scisignal.aal4501). Herein, we show that this prosurvival response is caused by the action of the channel-forming effector VopQ that targets the host V-ATPase, resulting in lysosomal deacidification and inhibition of lysosome-autophagosome fusion. Recent structural studies have shown how VopQ interacts with the V-ATPase and, while in the ER, a V-ATPase assembly intermediate can interact with VopQ, causing a disruption in membrane integrity. Additionally, we observed that VopQ-mediated disruption of the V-ATPase activates the IRE1 branch of the unfolded protein response (UPR), resulting in an IRE1-dependent activation of ERK1/2 MAPK signaling. We also find that this early VopQ-dependent induction of ERK1/2 phosphorylation is terminated by the VopS-mediated inhibitory AMPylation of Rho GTPase signaling. Since VopS dampens VopQ-induced IRE1-dependent ERK1/2 activation, we propose that IRE1 activates ERK1/2 phosphorylation at or above the level of Rho GTPases. This study illustrates how temporally induced effectors can work as in tandem as agonist/antagonist to manipulate host signaling and reveals new connections between V-ATPase function, UPR, and MAPK signaling. IMPORTANCE Vibrio parahaemolyticus is a seafood-borne pathogen that encodes two type 3 secretion systems (T3SS). The first system, T3SS1, is thought to be maintained in all strains of V. parahaemolyticus to maintain survival in the environment, whereas the second system, T3SS2, is linked to clinical isolates and disease in humans. Here, we found that first system targets evolutionarily conserved signaling systems to manipulate host cells, eventually causing a rapid, orchestrated cells death within 3 h. We have found that the T3SS1 injects virulence factors that temporally manipulate host signaling. Within the first hour of infection, the effector VopQ acts first by activating host survival signals while diminishing the host cell apoptotic machinery. Less than an hour later, another effector, VopS, reverses activation and inhibition of these signaling systems, ultimately leading to death of the host cell. This work provides example of how pathogens have evolved to manipulate the interplay between T3SS effectors to regulate host signaling pathways.